Modification of the schenck classification of knee dislocations based on a global consensus study - Scheepers, Waldo (Division of General Surgery, 2026)
Objectives: Knee dislocations (KD) are complex injuries defined as incongruity of the tibiofemoral joint which leads to tears of two or more of the main stabilizing knee ligaments, and they are often associated with damage to surrounding soft tissue or neurovascular structures. A classification system for these injuries should be simple and reproducible, and should allow communication among surgeons for surgical planning and outcome prediction. The energy-based classification and directional classification have been found inadequate in accurately classifying KD in a useful manner. Although the Schenck anatomic classification has improved on these earlier classifications, it is not without limitations. The aim of this study was to formulate a list of factors, prioritized by highvolume knee surgeons, that should be included in a KD classification system. Methods: A global panel of orthopaedic knee surgery specialists participated in a Delphi process. The first survey employed 91 orthopaedic surgeons to generate a list of patient and system-specific factors that should be included in a knee dislocation classification system that may affect surgical planning and outcomes. This list was subsequently prioritized in 2 further rounds by 27 identified experts (mean 15.3 years of experience) who could choose half of the factors that were identified in the first round. They were from Brazil (n=9), the United States of America (n=6), South Africa (n=4), India (n=4), China (n=2) and the United Kingdom (n=2). Experts were eligible for inclusion in the second and third rounds if they had at least 10 years of experience in knee surgery, or if they performed at least 10 KD surgeries annually. Participants in all 3 rounds were all members of the International Society of Orthopaedic Surgery and Traumatology (SICOT). Rounds occurred on a monthly basis, and all communication was done via email. The items were analysed to find factors that had at least 70% consensus for inclusion in a classification system. Results: Of the 12 factors identified, four (33%) achieved at least 70% consensus agreement for inclusion in a classification system. The factors deemed critical for inclusion in a classification system included: vascular injuries (89%), common peroneal nerve injuries (78%), number of torn ligaments (78%), and open injuries (70%). Conclusion: Consensus for inclusion of various factors in a knee dislocation classification system was not easily achieved. The wide geographic distribution of participants provides diverse insight and makes the results of the study globally applicable. The most important factors to include in a classification system as determined by the Delphi technique were vascular injuries, common peroneal nerve injuries, number of torn ligaments, and open injuries. To date, the Schenck anatomic classification system most accurately identifies these patient variables with the addition of the open injury classification. The authors propose to update the Schenck classification system with the inclusion of open injuries as an additional modifier, though this is only a small step in updating the classification and further studies should evaluate the inclusion of more advanced imaging modalities. Future research should focus on integrating these factors into a useful classification system that is predictive of surgical treatment and patient outcomes.